Buteyko Breathing Techniques and Asthma Gymnastics on Improving Oxygen Saturation and Eosynophile Levels among Asma Patients - Niya Fittarsih Fittarsih; Ari Suwondo; Rr. Sri Endang Pujiastuti; Bedjo Santoso (International Journal of Nursing and Health Services (IJNHS), 2021)
Asthma is a chronic disease of the respiratory system that causes respiratory symptoms, such as wheezing, shortness of breath and coughing, so that one of the non-pharmacological therapies can be used to help increase oxygen saturation, eosinophil levels and prevent recurrence independently by using the buteyko breathing technique and asthma gymnastics. This study aims to analyze the effectiveness of the buteyko breathing technique and asthma gymnastics on the improvement of oxygen saturation values ??and eosinophil levels. The study quasi experiment used a pre-test – post-test design with a control group design involving 36 asthma patients. Selected through a non- probability sampling technique with a purposive sampling method which is divided into 3 groups, namely 12 respondents in intervention group 1 who were given buteyko breathing technique treatment, 12 respondents in intervention group 2 who were given treatment in the form of buteyko breathing technique and asthma gymnastics, while 12 respondents in a control group that was only given asthma gymnastics. Measurements of oxygen saturation and eosinophil levels were carried out on the 1th, 7th to 14th day with 3 measurements, then the data were analyzed using the General Lineal Model (GLM) test. Repeated ANOVA test showed that there was a difference in the mean value of oxygen saturation (spo2) and eosinophil levels with a value of p = 0.000 which indicated that there was a significant difference between groups with the highest increase in oxygen saturation value in the intervention group 2 (Buteyko and asthma gymnastics) that is 1.83, followed by intervention group 1 (Buteyko breathing technique) that is 0.50 and the smallest decrease in the value of SpO2 was in the control group (asthma exercise) of 0.42. The highest decrease in eosinophil levels was in the intervention group 2 that is -21.66, followed by the control group that is -18.67 and the smallest decrease in eosinophil value was in the intervention group 1 at -7.66. Research conclusions buteyko breathing technique and asthma gymnastics effectiveness on value improvements oxygen saturation and eosinophil levels.